Performance Analysis of Fair Medium Access Control Protocol for Asymmetric Full Duplex in WLAN - Jin-Ki Kim (IEEE Access, 2020)
Full-duplex (FD) communication is capable of simultaneously transmitting and receiving data on the same frequency band. To effectively utilize FD in a wireless local area network (WLAN), one must use medium access control (MAC) protocols that consider the characteristics of FD. Many researchers have proposed and analyzed FD MAC protocols for WLANs. Most of this work revealed that as the number of nodes increases, the overall throughput decreases due to collisions. We have found, however, that with a smart MAC protocol, the throughput actually improves as the number of nodes increases. In this paper, we propose an asymmetric FD MAC protocol and then design an FD WLAN analytical model to evaluate saturation throughput. In our analytical model, we consider FD pair probability-the probability that a node capable of FD communication exists. To validate our model, we calculate FD pair probability values based on the modulation and coding scheme (MCS) levels and self-interference cancellation (SIC). We then analyze the effect of the FD pair probability on throughput. Simulation results verify the accuracy of our analytical model. Moreover, we compare the fairness of the proposed and conventional FD MAC protocols. As demonstrated through extensive evaluations, the fairness of the proposed FD MAC protocol is improved.